Designing residential aged care for people at risk of, or experiencing, homelessness: An exploratory Australian study. (26th April 2020) - Rowlands, Allison; Poulos, Roslyn; Agaliotis, Maria; Faux, Steven; Raguz, Angela; Poulos, Christopher
Abstract: The number of older people experiencing or at risk of homelessness, both long‐term and first‐time homelessness, is increasing. The proportion of women facing homelessness within that cohort is also increasing. When combined with complex health needs, appropriate long‐term care options remain limited. This qualitative study conducted in Sydney, Australia, aimed to explore the care needs of older people with comorbid health issues who are facing homelessness and, from this assessment, derive a preferred model of residential aged care. Interviews and focus groups were conducted with 29 participants from providers in the aged care and homelessness sectors. Data were analysed using a grounded theory approach. Causal and contextual factors, and consequences surrounding the experience of homelessness, informed the wide range of care needs of this group ( model of care ), and the organisational resources required to deliver them ( management issues and staff ). A trauma‐informed approach to care consistently applied by all staff to all processes throughout the care home was recommended. Such an approach would further strengthen existing models of care and take into account both health needs (such as mental health, substance dependence and acquired brain injury) and significant losses through the life course of this vulnerable population.